2016
DOI: 10.1007/s13205-016-0401-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CLA-producing Butyrivibrio spp. reveals strain-specific variations

Abstract: Conjugated Linoleic Acid (CLA), a fatty acid with high nutraceutical value is produced in rumen by resident bacterial species, especially Butyrivibrio spp. The present study was undertaken to examine the diversity of indigenous Butyrivibrio spp. from rumen liquor of Indian ruminants. The isolates were screened for their CLA production capability at different level of linoleic acid (LA) (0, 200, 400, 600, 800 μg/ml) at different time intervals (0, 2, 4, 6, 12, and 24 h). A total of more than 300 anaerobic cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Some B. fibrisolvens strains further convert this 18:2 isomer to trans-11 18:1, whereas trans-11,cis-15 18:2 is the end product of other strains (Fukuda et al, 2009). This suggests that biohydrogenation of 18:2n-6 and 18:3n-3 is strain specific, as observed by others (Gorissen et al, 2010;Hennessy et al, 2012;Hussain et al, 2016).…”
Section: Bacteria Involved In the Trans-11 Pathwaymentioning
confidence: 70%
See 2 more Smart Citations
“…Some B. fibrisolvens strains further convert this 18:2 isomer to trans-11 18:1, whereas trans-11,cis-15 18:2 is the end product of other strains (Fukuda et al, 2009). This suggests that biohydrogenation of 18:2n-6 and 18:3n-3 is strain specific, as observed by others (Gorissen et al, 2010;Hennessy et al, 2012;Hussain et al, 2016).…”
Section: Bacteria Involved In the Trans-11 Pathwaymentioning
confidence: 70%
“…Furthermore, Butyrivibrio spp. was suggested to isomerize 18:2n-6 to cis-9,trans-11 CLA more rapidly than any other bacterial species (Paillard et al, 2007;Shingfield et al, 2012;Hussain et al, 2016), although in most pure culture studies reported in Table 2, this could not be confirmed, as kinetic assessments were lacking. Furthermore, interexperiment comparisons of pure culture studies are challenging, due to diversity in growth media, which might affect the growth and biohydrogenating activity, as some bacteria might face suboptimal conditions.…”
Section: Bacteria Involved In the Trans-11 Pathwaymentioning
confidence: 95%
See 1 more Smart Citation
“…() and Hussain et al . () showed differences in LA metabolism among several tens of Butyrivibrio isolates, a large number being able to metabolize LA to VA. Slight differences in BH pathways between strains have also been found for ALA metabolism, MDT‐5, A38 and MDT‐10 strains producing trans ‐11, cis ‐13‐CLA, trans ‐11, cis ‐15‐C18:2 or VA, respectively, when incubated with ALA (Fukuda et al .…”
Section: Rumen Bh: a Microbiota Response To Dietary Ufasmentioning
confidence: 99%
“…This approach can be feasible by adding the ruminant's diet rich in LA and/or by supplementing the microbes directly into the rumen having potential of CLA production which ultimately lead to foods of animal origin with enhanced nutraceutical importance. A number of CLA producing bacteria of the rumen origin including Butyrivibrio fibrisolvens [12], lactic acid bacteria (LAB) namely Lactobacillus acidophilus, Lactococcus lactis subsp. cremoris, L. lactis subsp.…”
Section: Introductionmentioning
confidence: 99%